Hero stone with the hero mounted on a horse - Temples of India Project Team (Jio Institute, 2024)
Another small stone fragment, likely originally part of a larger hero stones, is now housed in the premises of the Suswani Mata Temple. This fragment is noticeably less ornate compared to the larger stone slabs. It depicts only two figures, one is the hero mounted on a horse, and the other is a figure standing with folded hands. The human figures are carved within rectangular niches on the fragment. There are no remaining traces of writing left on the lower side of this hero stones fragment.